A new multi robot search algorithm using probabilistic finite state machine and Lennard Jones potential function - Khan, Md. Shadnan Azwad (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2017.